African Charter at 30: A guide to the African Human Rights System (Pretoria University Law Press (PULP), 2011)
African Charter at 30: A guide to the African Human Rights System 2011 ISBN: 978-1-920538033 Pages:65 Print version: Available Electronic version: Free PDF available